LIABILITY FOR THE TRAFFIC OF AUTONOMOUS CARS IN THE CONTEXT OF THE PROTECTION OF HUMAN RIGHTS - Chłopecka, Antonina (Człowiek w cyberprzestrzeni, 2020)
At present, many countries (in particular the United States and the United Kingdom) carry out tests with autonomous vehicles and, under certain conditions, allow private individuals to use autonomous cars. As a result, legislation to provide for autonomous cars is gradually being drafted. It is worth deepening this issue in the context of a buoyant development of new technologies . Especially given that the rapid development of autonomous cars today links to liability for their movement, both in terms of civil traffic and the use of vehicles for military purposes. Accordingly, the above necessitates the rules of liability for the owners of these vehicles, their administrators and, finally, the countries which apply them in civil and military use. The definition of liability rules for the use of autonomous vehicles is particularly relevant in the context of the protection of human rights, in particular the right to life and health. Legal standards applicable to this issue should ensure an adequate level of protection of these rights. On this occasion, I wish to claim that the current rules do not suffice to solve the problems relating to autonomous vehicles - in particular, liability for damage caused by their operation.